DEVELOPMENT OF A LOW-COST BENCHTOP RESISTIVE FURNACE WITH ATMOSPHERE AND VACUUM CONTROL (Editora Impacto Científico, 2025)
The present study reports the development, assembly, and experimental validation of a bench-scale cylindrical resistance furnace capable of operating under controlled atmosphere and vacuum conditions, designed according to a low-cost and sustainable engineering approach. The system was constructed through the reuse and reconfiguration of an EMEC industrial furnace (model G28), originally divided into three independent heating zones, which were connected in series to operate at 220 V two-phase, with a total resistance of 22 Ω and nominal power of 2.2 kW. The NOVUS N1200 digital controller coupled with an SSR-4840 solid-state relay, operating in closed-loop PID mode, exhibited less than 1% overshoot and ±2 °C steady-state stability, ensuring high accuracy and reproducibility. Thermal tests demonstrated axial uniformity within ±5 °C up to 1000 °C, with heating times ranging from 30 to 220 minutes, depending on the temperature setpoint. The vacuum system achieved 1.2 × 10⁻³ Torr using a mechanical pump, and is projected to reach 10⁻⁶ Torr with the addition of a diffusion pump, enabling operation under vacuum or inert atmosphere (Ar 99.999%). After 20 complete thermal cycles, the furnace maintained structural integrity and electrical stability, confirming its robustness, efficiency, and reliability. The total manufacturing cost was approximately 30% of a comparable commercial furnace, highlighting the potential of this low-cost and sustainable design to strengthen scientific infrastructure for research in Advanced Materials and Metallurgy.DOI: https://doi.org/10.56238/edimpacto2025.090-053